Post-Pandemic Scenario of Incubation Centers and Entrepreneurs : A Review Article - Patowary, Bishal; Bora, Bhaskarjyoti (AMC Indian Journal of Entrepreneurship, 2025)
Purpose : The purpose of the study was to examine the COVID-19 scenario that entrepreneurs faced and its effect on the trade and commerce ecosystem. The focus was on how incubation centers contributed to the survival of startups and entrepreneurial institutions. Methodology : Through a survey of the literature, we attempted to concentrate on how well incubation centers functioned in fostering the entrepreneurship process throughout the state. Findings : During the pandemic, which gave a serious blow to corporate entities, business incubators offered a range of services, activities, guidance, and facilities that were important for the improvement of the performance of business firms, which was evident in the academic literature. Even though the entrepreneurs lacked financial support, they received all the business counseling and feasibility study services required for their development. Practical Implications : This article will help the incubators and the society at large, especially the entrepreneurs who are job creators and are self-reliant. Originality : Unlike previous studies on incubation practices, this research focused on the role of incubation programs in improving the lives of entrepreneurs through an exhaustive literature review.